Human Resource Planning - Ruchi Tripathi (AG Volumes, 2021)
Developing a competitive edge and increasing the capacity to compete in the market place requires an understanding of how to recruit, retain, and inspire the best and brightest employees. Moreover, a company must be able to implement overall quality management soft aspects in order to maintain a long-term competitive edge. Review of research, examining the impact on competitive advantage of human resource management methods and overall quality management procedures is the goal of this chapter.